Causes and consequences of a complex recombinational landscape in the ant Cardiocondyla obscurior - Errbii, Mohammed; Gadau, Jürgen; Becker, Kerstin; Schrader, Lukas; Oettler, Jan (Genome Research, 2024)
Eusocial Hymenoptera have the highest recombination rates among all multicellular animals studied so far, but it is unclear why this is and how this affects the biology of individual species. A high-resolution linkage map for the ant Cardiocondyla obscurior corroborates genome-wide high recombination rates reported for ants (8.1 cM/Mb). However, recombination is locally suppressed in regions that are enriched with TEs, that have strong haplotype divergence, or that show signatures of epistatic selection in C. obscurior. The results do not support the hypotheses that high recombination rates are linked to phenotypic plasticity or to modulating selection efficiency. Instead, genetic diversity and the frequency of structural variants correlate positively with local recombination rates, potentially compensating for the low levels of genetic variation expected in haplodiploid social Hymenoptera with low effective population size. Ultimately, the data show that recombination contributes to within-population polymorphism and to the divergence of the lineages within C. obscurior.
10.1101/gr.278392.123